Authority and knowledge in the pesantren-based madrasah curriculum: An archaeological and genealogical analysis of Michel Foucault - Ainun Hakiemah; Zulkipli Lessy; Karwadi Karwadi (Universitas Papua, 2026)
Pesantren-based Madrasah Aliyah has a strategic position as an institution that combines the national education system with the tradition of pesantren education. On the other hand, the standardization of the national curriculum, accreditation system, and administrative demands cause the autonomy space of Pesantren to be increasingly limited, giving rise to contestation between the interests of the state, the madrasah bureaucracy, and the kiai authority in determining the direction of the curriculum. This research is important to explain how the curriculum functions as an arena for power contestation as well as knowledge production through the perspective of archaeology and genealogy of Michel Foucault. The research uses an interpretive qualitative approach with a multi-locus study design on three Islamic boarding school-based MA in the Special Region of Yogyakarta. The results of the study show that the curriculum is an arena for the production of power-knowledge that produces different configurations of power in each madrasah. MA Al-Jauhar and MA Sunan Pandanaran show the strengthening of the role of madrasas as centers of knowledge production through curriculum synthesis, while MA As-Salafiyyah maintains the epistemic dominance of pesantren through the substitution of state subjects with the yellow book. These findings confirm that curriculum implementation is a dynamic negotiation process between state standardization, madrasah autonomy, and pesantren authorities.